A look at the role of mucilage at the industrial level - Villega Calero, María Paz (2021)
Introduction: This bibliographic review gathers information regarding mucilages, their characteristics, extraction methods for various plant species, and their uses at a pharmaceutical level and for other industries. Methods: This bibliographic review compiles documents printed before December 2020, were searched using Elsevier and Google Scholar databases. Studies that examined mucilages that were not derived from plants were excluded from this review. Results: Mucilages have properties that allow them to be used as excipients in pharmaceutical preparations. They also have pharmacological activities, and have applications in the cosmetics and food industries. Conclusion: The use of mucilages provides numerous benefits, particularly to the pharmaceutical industry.